Knowledge of the Anxiety Level of Clients with Chronic Kidney Failure - Lailatul Badria; Fatmawati Fatmawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: Anxiety is an individual's response to an unpleasant situation. The response that arises in anxiety is worry, restlessness, and can be accompanied by physical complaints. Conditions are experienced subjectively and communicated in interpersonal relationships. The level of knowledge possessed makes a person better able to cope with changes in their health status. Objective: This study aims to determine the relationship between knowledge and the anxiety level of chronic kidney failure clients. Method: This research uses an analytical survey method with a cross-sectional study approach. The number of samples used was 33 respondents. The results of the study show a p-value of 0.001. Conclusion: There is a relationship between knowledge and the anxiety level of clients with chronic kidney failure, so it is better for health workers who have direct contact with kidney failure patients to provide more interventions to increase patient knowledge.